Innovative Approaches to Native Language Instruction in Early Childhood Education to Support Sustainable Development Goals for Quality Education - Ergasheva, Gulrukhsor Surkhonidinovna; Mirzaeva, Farokhat Odiljonovna; Abdullayeva, Maryambibi Djumaniyazovna; Utbasarova, Umida Mekhmanovna; Mutalova, Dilnoza Abdurashidovna; Farmonov, O'ktam Ne'matovich (International Journal of Language Education, 2025)
This study aimed to explore innovative methods for native language instruction in early childhood to improve quality education in line with the Sustainable Development Goals (SDGs). A mixed-method design was used, involving 60 preschool teacher trainees divided into experimental and control groups. The experimental group received 12 weeks of training using storytelling, multimedia, and play-based strategies. Results showed significant gains in language proficiency, engagement, and teacher confidence in the experimental group. These methods proved effective because they encouraged child participation, contextual learning, and creativity. Integrating child-centered approaches with technology not only enhanced language development but also empowered future educators to create inclusive, high-quality learning environments.